CAD for interiors basics - Fiorello, Joseph A. (Hoboken, New Jersey : Wiley, 2009)
CAD for Interiors: Basics is a practical guide to getting started in AutoCAD(r) for interior designers. Taking a hands-on approach, the reader is taken on a step-by-step process to draw a detailed building floor plan. Beginning with instruction on how to create project templates, the reader works their way up to a professional-quality presentation. The basics of Architectural Desktop(r) and 3-D CAD are also included. An included DVD complements the book, presenting videos of detailed AutoCAD(r) commands demonstrating the book's instruction using a unique audio-visual approach. No other product for designers offers a blended approach to make learning visually exciting and effective.
Preface -- Acknowledgements -- Introduction -- 1. Interacting with Autocad -- 2. Preparing to draw -- 3. Drawing a base plan -- 4. Adding text and dimensions to a drawing -- 5. Adding layers to a drawing -- 6. Adding to the base plan -- 7. Drawing interior sections and elevations -- 8. Creating a titleblock and template file -- 9. Layout space and plotting a drawing -- 10. Introduction to google sketchup.
Includes index.
Keywords: INTERIOR DECORATION